2013
DOI: 10.1002/lary.21891
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric temporal bone fractures: Current trends and comparison of classification schemes

Abstract: In this pediatric series, approximately 75% of the fractures are longitudinal and 25% are transverse. The otic capsule is spared in 90% and violated in 10%. Both OCS/OCV and L/T classification schemes predict SNHL, but the OCV/OCS scheme is more accurate in this prediction. Although the negative predictive value of the two schemes is similar, the positive predictive value is higher with the OCS/OCV system. The presence of conductive hearing loss and facial nerve symptoms was not predicted by either classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 9 publications
1
30
2
Order By: Relevance
“…Motor vehicle accidents are more commonly associated with temporal bone fracture in younger children . In approximately 50–74% of cases, the fractures were classified as longitudinal, 12.5–24% as transverse and 37.5% as mixed ones . In the series by Wexler et al ., 10 of 40 children with temporal bone fracture had sequel; 2 children (5%) had FNP, 6 children (15%) had conductive hearing loss and 2 had sensorineural hearing loss (5%).…”
Section: Discussionmentioning
confidence: 99%
“…Motor vehicle accidents are more commonly associated with temporal bone fracture in younger children . In approximately 50–74% of cases, the fractures were classified as longitudinal, 12.5–24% as transverse and 37.5% as mixed ones . In the series by Wexler et al ., 10 of 40 children with temporal bone fracture had sequel; 2 children (5%) had FNP, 6 children (15%) had conductive hearing loss and 2 had sensorineural hearing loss (5%).…”
Section: Discussionmentioning
confidence: 99%
“…Although both systems are accurate in predicting SNHL, describing fractures in terms of otic capsule involvement increases the accuracy and positive predictive value. 63 Regardless of the classification system used, CT plays an essential role in the diagnosis and management of pediatric temporal bone fractures. Correlative MR studies may provide additional information about intracranial injury, potential cerebrospinal fluid fistula, brain herniation, and possibly facial nerve integrity.…”
Section: Temporal Bone Fracturesmentioning
confidence: 99%
“…62 Temporal bone fractures have been classically described as longitudinal or transverse in nature, with longitudinal fractures occurring 80% to 90% of the time. 63 In an attempt to further refine the classification system and predict SNHL, fractures have been further categorized as otic capsule violating or otic capsule sparing. Using this system, 90% of temporal bone fractures are described as otic capsule sparing, with the remainder violating the otic capsule.…”
Section: Temporal Bone Fracturesmentioning
confidence: 99%
“…The most common cause of pediatric temporal bone trauma is motor vehicle accidents. Therefore, the second cause of falls is usually associated with skull fractures such as parietal, sphenoid, frontal, occipital, ethmoid, orbital roof/ wall, and others [19][20][21]. Waissbluth et al [19] reported that hemotympanum, decreased or loss of consciousness, and headache were the most prevalent clinical presentation due to high impact trauma.…”
Section: Management Of Pediatric Ear Traumamentioning
confidence: 99%